Latino Veterans with PTSD: A Systematic Review - James O. E. Pittman (Behavioral Sciences, 2014)
Latinos have a long history of military service with recent service including combat conditions and multiple deployments, which are highly associated with posttraumatic stress disorder (PTSD). Clinical acumen underscores the importance of culture in assessment and treatment, but there has been little scientific literature that investigates the unique needs of veteran Latinos with PTSD. The primary goal of this systematic review was to analyze the existing literature on Latino veterans with PTSD and to critically evaluate attention to cultural issues. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses were used to guide this review. Peer-reviewed, research reports written in English on Latino Veterans with PTSD since 1980 were included; 20 were assessment related, and nine were treatment related. All studies were quantitative. Only 13 studies mentioned culture as part of the context for Latino veterans, and only seven included cultural factors as part of the study design. Present findings highlight a lack of research focused on understanding cultural factors related to the assessment and treatment of Latino veterans with PTSD. Culturally-informed research on Latino veterans from current wars, Latina veterans and Latino veteran treatment outcomes are necessary to provide culturally-appropriate care to this growing veteran subgroup.